Implications of Excellence in Research and Teaching - Wespel, Johannes; Orr, Dominic; Jaeger, Michael (International Higher Education, 2013)
Stratification of higher education is currently being driven by public funding schemes, among other things. Building on a survey of excellence funding initiatives across OECD member countries based on the measurement of excellence in higher education institutions, this contribution focuses on how teaching and learning are integrated into these highly selective funding mechanisms. It turns out that teaching performance is generally much less significant than research. Possible reasons and consequences for this result are discussed.